2021
DOI: 10.1002/2050-7038.13091
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental validation of novel robust MPPT controller based on bond graph and fuzzy logic for PV system under variable weather conditions

Abstract: Traditional MPPT algorithms have demonstrated effective performance relative to their flexibility and simplicity of implementation. However, its main disadvantages are the ineffectiveness and the large oscillations around the MPP under non-uniform solar irradiance. To achieve better performance in the power extraction from the PV system, we propose in this work a new hybrid controller focused on the bond graph and fuzzy logic (BG-FL-MPPT) to track the maximum power point under different weather conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The new controller could track and find the optimal efficiency point in the system. The experimental results showed that the stability and robustness of the new algorithm controller were much higher than those of traditional algorithm controllers (Badoud et al, 2021). Bhukya and Nandiraju found that traditional algorithms couldn't fully track the optimal power point due to the randomness and intermittency of photovoltaic systems.…”
Section: Related Workmentioning
confidence: 97%
“…The new controller could track and find the optimal efficiency point in the system. The experimental results showed that the stability and robustness of the new algorithm controller were much higher than those of traditional algorithm controllers (Badoud et al, 2021). Bhukya and Nandiraju found that traditional algorithms couldn't fully track the optimal power point due to the randomness and intermittency of photovoltaic systems.…”
Section: Related Workmentioning
confidence: 97%
“…The MPPT efficiency is the percentage ratio between the PV array's actual output power and expected output power (22). A PV system's MPPT efficiency is measured using two different schemes: static MPPT and dynamic MPPT (23). An MPP tracker's static MPPT efficiency is calculated by applying a static or constant irradiance profile to the PV system's power stage.…”
Section: Experimental Analysis For Adaptation Of Mppt For Sc-battery ...mentioning
confidence: 99%
“…Solar energy is the abundant, most prominent, inexhaustible, and clean as compared to the non-REs sources [3]. These sources rely on environmental conditions for power generation, such as temperature and irradiance [4]. The SE has become the prime area of active research due to the aforementioned features and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of the system depends upon the non-renewable energy resources. Though these resources fulfil the energy demands but they also add some harmful effects to environment, i.e., they generate harmful gases which deplete the ozone layer, beside this these resources depend upon the fossils fuels which are depleting rapidly [4]. Due to environmental concerns and the ending fossil fuels, researchers tend to create new energy resources that can overcome the environmental issues as well as has a long-lasting nature.…”
Section: Introductionmentioning
confidence: 99%